Effects of propranolol on response to exercise in hypertrophic obstructive cardiomyopathy. - Edwards, R; Kristinsson, A; Warrell, D; Goodwin, J (1970)
The circulatory, respiratory, and metabolic responses to steady state submaximal exercise have been studied in four women and two men with hypertrophic obstructive cardiomyopathy, before treatment, after intravenous, and after three months of oral propranolol. The physical working capacity was significantly lower than in normal subjects, and the response to exercise was characterized by a tachycardia, low cardiac output and stroke volume, and high ventilation and blood lactate concentration. After propranolol there was a significant reduction in heart rate, but changes in most other measurements were slight and there was no improvement in effort tolerance though angina was relieved in the two patients in whom it was present. The possible causes of breathlessness and effort intolerance in hypertrophic obstructive cardiomyopathy are discussed in relation to known effects of propranolol. It is concluded that further trial of propranolol and other beta-adrenergic blocking agents is warranted.